Uninked paintings, sculpture and graphic works by 5 contemporary cartoonists : Kim Deitch, Jerry Moriarty, Gary Panter, Ron Regé, Jr., Seth : with supplementary readings : Marshall Gallery of Contemporary Art, The Phoenix Art Museum, April 21-August 19, 2007 - Ware, Chris 1967- (Phoenix Art Museum, 2007)
Five of the finest cartoonists currently working are also, not surprisingly, five of cartooning's finest artists. While the original ink-on-paper drawings which compose literary graphic novels and comic strips are generally only one step in the arduous process of creating a visual book, they are not necessarily intended to be seen as finished works in and of themselves. This exhibit chooses instead to focus on those artists whose work intentionally already extends beyond the page: rarely-seen drawings, paintings, lithographs, and sculptures which develop the extensive narrative worlds and ideas which every cartoonist has spent years, and in some cases, lifetimes, developing. The prolific artists presented -- Kim Deitch, Jerry Moriarty, Gary Panter, Ron Regé, Jr. and Seth -- have all devoted themselves to their imaginative work with an multifarious intensity at a time when a great deal of contemporary art mines its so-called visual "source material" from narrative popular culture but then chooses to blur or disregard its story content before enlarging it onto a gallery wall. By contrast, the work by these five artists -- for whom storytelling is second nature -- is unusually original, direct and full of life.
Keywords: Panter, Gary -- 1950-; Regé, Ron -- 1969-; Seth -- 1962-; Deitch, Kim -- 1944-; Moriarty, Jerry -- 1938-; Art, American / Exhibitions; Cartoonists / North America; Art, American; Cartoonists; North America; Bandes dessinées / États-Unis / 20e siècle; Dessinateurs de bandes dessinées / États-Unis; Exhibition catalogs; Ausstellungskatalog -- Phoenix Art Museum -- 21.04.2007-19.08.2007 -- Phoenix, Ariz.